In Vivo and Ex Vivo Pediatric Brain Tumor Models: An Overview - Li, Zhiqin; Langhans, Sigrid A. (Frontiers in Oncology, 2021)
After leukemia, tumors of the brain and spine are the second most common form of cancer in children. Despite advances in treatment, brain tumors remain a leading cause of death in pediatric cancer patients and survivors often suffer from life-long consequences of side effects of therapy. The 5-year survival rates, however, vary widely by tumor type, ranging from over 90% in more benign tumors to as low as 20% in the most aggressive forms such as glioblastoma. Even within historically defined tumor types such as medulloblastoma, molecular analysis identified biologically heterogeneous subgroups each with different genetic alterations, age of onset and prognosis. Besides molecularly driven patient stratification to tailor disease risk to therapy intensity, such a diversity demonstrates the need for more precise and disease-relevant pediatric brain cancer models for research and drug development. Here we give an overview of currently available in vitro and in vivo pediatric brain tumor models and discuss the opportunities that new technologies such as 3D cultures and organoids that can bridge limitations posed by the simplicity of monolayer cultures and the complexity of in vivo models, bring to accommodate better precision in drug development for pediatric brain tumors.